Viral Anxiety Mediates the Influence of Intolerance of Uncertainty on Adherence to Physical Distancing Among Healthcare Workers in COVID-19 Pandemic - Chung, Seockhoon; Lee, Taeyeop; Hong, Youjin; Ahmed, Oli; Silva, Washington Allysson Dantas; Gouin, Jean-Philippe (Frontiers in Psychiatry, 2022)
Introduction The aims of this study were to examine the mediation effect of viral anxiety of healthcare workers on the influence of their intolerance of uncertainty on the adherence to physical distancing during the COVID-19 pandemic. Methods An online survey was conducted among 329 healthcare workers (female: 81.4%, nursing professionals: 59.0%, and shift workers: 22.3%) on November 29, 2021. Participants responded to questionnaires on adherence to physical distancing, health beliefs, and perceived social norms, and rating scales of the Stress and Anxiety to Viral Epidemics-6 items (SAVE-6), Patient Health Questionnaire-9 items (PHQ-9), and the Intolerance of Uncertainty-12 items (IUS-12) scale. Results Adherence to physical distancing of healthcare workers was predicted by perceived benefits of physical distancing (β=0.13, p=0.01), personal injunctive norms (β=0.32, p<0.001), SAVE-6 score (β=0.13, p=0.02), and IUS-12 score (β=0.10, p=0.045) (adjusted R2=0.21, F=22.3, p<0.001). Viral anxiety mediated the association between intolerance of uncertainty and adherence to physical distancing but not the influence of perceived benefits and personal injunctive norms on adherence to physical distancing. Conclusion We observed that viral anxiety of healthcare workers mediated the association between intolerance of uncertainty and adherence to physical distancing. During this pandemic, exploring adherence to physical distancing and its predicting factors will be helpful for the safety of healthcare workers and the patients for whom they care.